SOCIAL STUDIES LESSONS ACCORDING TO CRITERIA EVALUATION OF THE USE OF CARTOON - Erol KOÇOĞLU (International Journal of Eurasia Social Sciences, 2016)
Visual literacy has been considered as one of most important skills that are expected to bring in educational environments due to visuals’ increasing effect on daily life. There are various contributions of visuals to educational environments. The important examples of those contributions are activating knowledge, integrating knowledge, facilitating understanding, constructing in the mind, and facilitating remembering what is learnt. For this reason, visual reading and visual presenting was integrated in Social Sciences Course Program beside the effect of constructivist approach. Visuals based on humor, especially cartoons, may positively affect attitude as well as academic achievement. Therefore, social sciences learning areas should be supported with visuals like cartoons for the skills of listening/watching, speaking, reading, and writing. In this study, it was investigated that how using cartoons in social sciences course affect academic achievement, attitude towards course itself, and permanence of what is learnt. For this reason, an experimental study including pre-test, post-test, and experimental and control groups was done.